Respiratory syncytial virus hospitalisation burden in children below 18 years in six European countries (2016-2023) pre- and post-COVID-19 pandemic - Ombeline Jollivet; Arantxa Urchueguía-Fornes; Kocfa Chung-Delgado; Caroline Klint Johannesen; Toni Lehtonen; David Gideonse; Rachel A. Cohen; Rolf Kramer; Alejandro Orrico-Sánchez; Thea K. Fischer; Terho Heikkinen; Michiel Van Boven; et al. (International Journal of Infectious Diseases)
Objectives: Respiratory syncytial virus (RSV) is a substantial cause of hospital admission in young children and leads to seasonal pressure on pediatric emergency units in most countries. This study aims to assemble national or large-scale data on RSV hospitalisations from six European countries with a standardised approach to provide recent burden data for all children and assess changes since SARS-CoV-2’s emergence. Methods: We analysed 2016-2023 hospital records from national registries in Denmark, England, Finland, The Netherlands, and Scotland, and from a hospital surveillance network in Spain-Valencia for children below 18 years. We considered separately RSV-coded and RSV laboratory-confirmed cases, comparing them to respiratory tract infections. We studied the temporal evolution of incidence rates and case reporting practices, comparing pre- and post-COVID-19 periods. Results: Post-COVID-19 observed RSV hospital burden was similar to the pre-COVID-19 one for younger children but higher for the 1-2 years, 3-4 years, and 5-17 years age groups. No change in terms of coding—neither diagnosis nor RSV-coding when RSV was laboratory-confirmed—was detected. Conclusions: Hospital RSV burden in children is significant but currently not fully monitorable. Further efforts to harmonise coding practices both within and across countries would improve the quality of future analyses. Additional data in future seasons should complement current outcomes to inform decisions regarding RSV prevention.